(untitled) (MSW Management Journal, 2026)
The rapid integration of sophisticated digital technologies has contributed to the enhancement of ethical issues in technology-based organizations and has raised a significant demand to comprehend the impacts of internal organizational designs on ethical decision-making and sustainable development. Although digital ethics have been widely discussed, there is little empirical evidence of the interaction between ethical maturity, organizational hierarchy, and the scalability of business enterprise. To fill this gap, the current study constructs and tests a Structural Equation Model (SEM) to test the determinants of ethical decision-making in technology-intensive settings. The quantitative, cross-sectional research design was adopted based on survey data on 150 professionals involved in software companies, AI-development organizations, and digital service companies. To test the relationships proposed, Partial Least Squares -Structural Equation Modeling (PLS-SEM) was used. The evaluation of measurement models indicated high reliability and validity, as all Cronbach Alpha values were more than 0.84 and all Average Variance Extracted (AVE) values were beyond the 0.50 level. The analysis of the structural model showed that Ethical Maturity has a strong positive impact on Business Scalability (β =0.54, p < 0.001), and 58% of the variation in the growth results can be explained by Ethical Maturity (R2 = 0.58). Furthermore, Organizational Hierarchy was identified to moderate this association considerably in a negative interaction (β= -0.32, p <0.05), thus confirming the existence of an ethical bottleneck as a result of hierarchy. The predictive relevance was established at a Stone Geisser Q2 value of 0.38, which implies a high model strength. The results highlight the fact that ethical maturity is a strategic resource for scalable expansion, and strict hierarchical forms of organization hinder decentralized ethical responsiveness. The current research provides empirical evidence that ethical leadership can be integrated with flexible organizational designs that will accelerate the process of responsible innovation within technology-focused organizations.